Implementation of Amaliyah Tadries in Shaping the Character of IDIA Students as Prospective Devoted Teachers - Luthfatul Qibtiyah; Ulya Mufliyati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Amaliyah Tadries is (teaching practice) a form of teaching practice by a prospective teacher in a guided manner to gain teaching skills. This activity is taken within a certain time as one of the requirements to fulfill the Niha'ie program. The uniqueness of the Amaliyah Tadries activity is able to shape the character of Candidate Intenship teachers including time discipline, and responsibility. The problems in this study are: 1) How is the implementation of Amaliyah tadries in shaping IDIA mahasantri as prospective service teachers 2) What are the supporting and inhibiting factors in the Amaliyah Tadries program in shaping the character of IDIA mahasantri as prospective service teachers. The objectives in this study are: 1) to find out how the implementation of Amaliyah Tadries in shaping IDIA students as Candidate Intenship teachers 2) to find out whether there are supporting and inhibiting factors in the Amaliyah Tadris program in shaping IDIA students as Candidate Intenship teachers. This research uses a qualitative approach with a descriptive type, data collection techniques in this research using interviews, observation, documentation, while the informants in this study came from the person in charge of Amaliyah Tadries, Musyrifah, Naiba musyrifah, and intensive final class students.